Proceedings of the 19th International Conference on Computational Linguistics - 2002
DOI: 10.3115/1072228.1072304
|View full text |Cite
|
Sign up to set email alerts
|

Using language and translation models to select the best among outputs from multiple MT systems

Abstract: This paper addresses the problem of automatically selecting the best among outputs from multiple machine translation (MT) systems. Existing approaches select the output assigned the highest score according to a target language model. In some cases, the existing approaches do not work well. This paper proposes two methods to improve performance. The rst method is based on a m ultiple comparison test and checks whether a score from language and translation models is signicantly higher than the others. The second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 6 publications
1
35
0
Order By: Relevance
“…Several studies have shown that the overall performance of the competitive arrangement can in fact, as hoped, be better than that of the best participating MT engine (Hogan and Frederking 1998;Cavar, et al 2000;Akiba et al 2002).…”
Section: Mt and The Usermentioning
confidence: 99%
“…Several studies have shown that the overall performance of the competitive arrangement can in fact, as hoped, be better than that of the best participating MT engine (Hogan and Frederking 1998;Cavar, et al 2000;Akiba et al 2002).…”
Section: Mt and The Usermentioning
confidence: 99%
“…Different approaches have been proposed and experiments conducted to combine results from multiple systems (Nirenburg & Frederlcing, 1994;Tidhar & Kiissner, 2000;Akiba et al, 2002;Callison-Burch & Flournoy, 2001;Nomoto, 2004;Jayaraman & Lavie, 2005;Matusov et al, 2006;Rosti, et al, 2007;Chen et al, 2007). MEMT has the potential to achieve significantly better performance than any single MT system (Callison-Burch, et al, 2008).…”
Section: Translation Strategies For Metadata Recordsmentioning
confidence: 99%
“…This approach does not take into account the transition between fragments. Statistical approaches (Kaki et al 1999;Callison-Burch and Flournoy 2001;Akiba et al 2002;Imamura et al 2004) select translation fragments with a statistical model. The statistical model can solve the transition problem by using n-gram co-occurrence statistics.…”
Section: Translation Generationmentioning
confidence: 99%